Hebrews 6:4-8: A socio-rhetorical investigation (Part 1) - DeSilva, David A. (Tyndale bulletin, 1999)
Socio-rhetorical interpretation pursues a richly textured exegesis of Scripture through co-ordinating multiple methods of reading and investigating texts. This interpretive model is put to the test as it is applied to Hebrews 6:4-8. In this, the first instalment of a two-part article, Hebrews 6:4-8 is analysed within the contexts of classical rhetoric, Jewish and Graeco-Roman intertexture, and prominent aspects of the first-century social and cultural environment. This passage presents an argument ‘from the contrary’ supporting the author’s deliberative agenda of promoting commitment to Jesus and fellow believers, drawing heavily on the social codes of patronage obligations as well as a wide spectrum of intertextual resources. Perseverance is shown to be the only just and expedient course of action, since it alone preserves obligations of gratitude. Part 2 of this article (to appear in Tyndale Bulletin 50.2) will examine the ideology promoted within the passage and how it contributes to the author’s rhetorical goals. A final section will attempt to answer the questions raised by the investigation of the social context of ancient patronage for the appropriateness of such ideological constructs as ‘eternal security’ or ‘unpardonable sin’ when applied in an absolute sense to the dynamic relationship between God and God’s clients.